PENGARUH KUALITAS AUDITOR TERHADAP KUALITAS AUDIT LAPORAN KEUANGAN (Studi Empiris Sebelum dan Setelah Pandemi COVID-19 Pada Auditor Kantor Akuntan Publik di Kota Semarang) - Tri Sukma Wiranti; Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2022)
This study aims to analyze empirically the differences in the relationship before and after COVID-19 between Auditor Independence, Auditor Competence, and Auditor Experience on Audit Quality of financial statement. The population in this study is the auditor of the Certified Public Accounting Firm (CPA) in the city of Semarang. The number of samples used in this study was 80 respondents from 19 CPAs taken through a purposive sampling technique.The results of this study indicate that: (1) Auditor Independence, Auditor Competence, and Auditor Experience partially have a positive and significant effect on Audit Quality under normal conditions (before COVID-19). As for the COVID-19 condition, Auditor Competence, Auditor Experience partially has a positive and significant effect on Audit Quality, while Auditor Independence has no significant positive effect. Simultaneously Auditor Independence, Auditor Competence, and Auditor Experience affect Audit Quality. (2) the independent sample t-test partially shows the results of Auditor Independence, Auditor Competence does not have a significant difference both before COVID-19 and after COVID-19. Meanwhile, Auditor Experience has a significant difference. Simultaneously, there is no significant difference between Auditor Independence, Auditor Competence, and Auditor Experience in Audit Quality.